2016
DOI: 10.1108/ijse-01-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities among malnourished children in India

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Employing the decomposition approach, a study concluded that maternal factors improve WAZ among children aged 0–5 years in India [ 27 ]. In other studies also, the role of mother’s education in explaining the inequalities in underweight was highlighted in Indian settings [ 29 , 35 ]. Of the environmental factors, defecation remained the highest contributor to the inequality in underweight with nearly 17%, during both the time-periods.…”
Section: Discussionmentioning
confidence: 96%
“…Employing the decomposition approach, a study concluded that maternal factors improve WAZ among children aged 0–5 years in India [ 27 ]. In other studies also, the role of mother’s education in explaining the inequalities in underweight was highlighted in Indian settings [ 29 , 35 ]. Of the environmental factors, defecation remained the highest contributor to the inequality in underweight with nearly 17%, during both the time-periods.…”
Section: Discussionmentioning
confidence: 96%
“…Our results were in line with the results of other studies that showed household economic status was the most important determinant influencing inequality in malnutrition. The percentage of economic status contribution or its proxy to malnutrition inequality has been reported to be 70% in Mozambique (27), 65% to 70% in Vietnam (9), 46% in Ghana (28), and 50% to 65% in India (3,7). In comparison with having access to health care, promoting socio-economic status is far more effective on health indices and outcomes, especially on the reduction of child mortality and improving their nutritional status (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this inequality among countries, there are also socioeconomic inequalities within countries and children in lower social groups bear a greater burden of malnutrition. Nutritional status of children is affected by many socioeconomic factors such as mother's education and nutritional status, residential area, household wealth, and demographic characteristics (3)(4)(5)(6)(7)(8)(9). For the first time in Iran, the concentration index and decomposition method was used to analyze the socio-economic inequalities in child mortality at the national level and with regard to the provinces (10).…”
Section: Introductionmentioning
confidence: 99%
“…Household wealth quantile (middle) contributed to the compositional rise of underweight, while richer contributes to the compositional decline of underweight in line with studies conducted in Vietnam and India (Kien et al, 2016, Srivastava, 2019, Mussa, 2014. This is known to be poor households often difficult to access food, and inadequate resource for care and unable to utilize the creation of sustainable health settings for their children (Akombi et al, 2017b, Prakash andJain, 2016). Also, age of child increased, the risk of deteriorating underweight were increased in line with studies (Abdollah ALMASIAN KIA 2019, CHAO, 2017, Kien et al, 2016, Srivastava, 2019.…”
Section: Discussionmentioning
confidence: 54%